Analysis of Factors Influencing The Decision to Choose The Department in The Natural Science Campus - Muhammad Hasan Sidiq Kurniawan; Achmad Fauzan; Jaka Nugraha (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Education is very important thing for everyone. Parents tend to choose high-quality school or campus, to ensure their children’s education. One thing which determined parents to choose the campus for their children is the prospect for work. Faculty of Natural Science UII have high-quality department. Some of them already had highest accreditation level and even Internationally accredited. But some peoples in Indonesian often asked about what become of their children after graduated from the faculty of natural science or what is job that suit for their chlidren. The department of that faculty often not become the first choice when choosing campus. Therefore, the research to study about factors which determine people to choose their college department is needed. In this paper, the study is focused on factors which influence people’s decision score to choose the department in the faculty of natural science. We are using correlation and regression analysis. The result show that factors which influence the people’s decision are different between one department with another. Those factor consist of: product, promotion, and the price/cost.